Arctic Ice‐Ocean Coupling and Gyre Equilibration Observed With Remote Sensing - Sarah Dewey; James Morison; Ronald Kwok; Suzanne Dickinson; David Morison; Roger Andersen (Geophysical Research Letters)
Abstract Model and observational evidence has shown that ocean current speeds in the Beaufort Gyre have increased and recently stabilized. Because these currents rival ice drift speeds, we examine the potential for the Beaufort Gyre's shift from a system in which the wind drives the ice and the ice drives a passive ocean to one in which the ocean often, in the absence of high winds, drives the ice. The resultant stress exerted on the ocean by the ice and the resultant Ekman pumping are reversed, without any change in average wind stress curl. Through these curl reversals, the ice‐ocean stress provides a key feedback in Beaufort Gyre stabilization. This manuscript constitutes one of the first observational studies of ice‐ocean stress inclusive of geostrophic ocean currents, by making use of recently available remote sensing data.